Phytochemical Screening and In Vitro Antioxidant Activity of Premna Serratifolia L. Leaf Extracts (International Journal of Food and Nutritional Sciences, 2021)
The current work is based on the study of the antioxidant properties of Premna serratifolia L. P. serratifolia is a small shrub that belongs to the family Lamiaceae which has a high degree of medicinal properties and hence they are used for the treatment of several diseases. Phytochemical screening of leaf extracts showed the existence of various phytochemicals like tannins, alkaloids, resins, phenols, and coumarins. Antioxidant properties of P. serratifolia were assessed by DPPH as well as ABTS radical scavenging activity.